The Involvement of Reactive Oxygen Species in Causing Chronic Cardiovascular and Neurodegenerative Diseases and Some Cancers - Tiwana, Jasneet K; Shah, Anureet K; Dhalla, Naranjan S (Scripta Medica, 2024)
An increase in the occurrence of different infectious and chronic diseases as well as aging population has resulted in poor human health and decline in the quality of life all over the world. In fact, chronic diseases, which are partially resistant to currently available drugs are long lasting health hazards and require ongoing medical attention. Major causes of increase in these diseases are considered to be changes in the environment as well as diets and lifestyle. Particularly, there has been changes from a simple, nutritious, low- calorie diet and active lifestyle to a complex and processed food rich in high calories accompanied by a sedentary lifestyle and unhealthy living habits. Since high-calorie diets and inactive lifestyle are known to promote the production of reactive oxygen species (ROS) in the body, it is likely that oxidative stress and associated inflammation may be intimately involved in enhancing the resistance of several disorders to the existing therapeutic interventions and thus promoting the occurrence of chronic diseases. A thorough review of literature regarding the pathogenesis of some major chronic diseases including cardiovascular disease like heart failure, neurodegenerative disorder like Alzheimer’s disease and various types of cancer has revealed that these health hazards are associated with increased oxidative stress, production of pro-inflammatory chemicals such as nitric oxide and some cytokines, as well as formation of some toxic substances such as advanced glycation end products. It is thus evident that extensive research work by employing genetic, immunological and nutraceutical approaches, needs to be carried out for developing some novel antioxidants with anti-inflammatory activities for reducing the incidence of chronic diseases. In the meantime, it would be prudent for patients with chronic diseases to pursue the preventive measures involving reduced intake of high calorie diet and following an active lifestyle.